(untitled) (Journal of Nobel Medical College, 2019)
Background: Fissures of lungs facilitate the movement of lobes which helps in expansion of lungs during breathing. The fissures may be complete, incomplete or absence. Sometime the accessory fissures may also present. Awareness of variations is essential during segmental resections as well as during radiological interpretation of lungs. Hence, the present study was aimed to study the morphological variations in fissures and lobes. Material and Methods: This study was consisted of sixty nine human lungs with irrespective of sex which were available in the department of anatomy of various medical colleges. All lung specimens were carefully observed and recorded for the presence of any variations in fissures and lobes. Results: The present study revealed that the absence of horizontal fissure was observed in 7.89%, while no specimen showed absence of oblique fissure on both sides. 35.48% of left lungs had incomplete oblique fissure compared to 28.95% of the right lungs. In addition, 22.58% of right lungs and 23.68% of left lungs showed presence of accessory fissure and lobes. From above, the incomplete and absent horizontal fissure was the most common abnormalities observed in this study. The accessory fissures were more common in lower lobe of right lung whereas in left lungs it was more common in upper lobe. Conclusion: The present study showed the wide range of variations in fissures and lobes of lungs. The knowledge of variations in morphology of lungs would be helpful for clinical diagnosis and pulmonary surgical procedures.